WOMEN'S RIGHTS VIOLATIONS IN THE PRACTICE OF VIRGINITY TESTING CONDUCTED BY THE INDONESIAN NATIONAL ARMED FORCES AND THE INDONESIAN NATIONAL POLICE FORCE - Valerie Selvie Sinaga; Michael Adrian Young (Awang Long Law Review, 2023)
Virginity testing is a practice that is discriminatory, degrading to the honor and dignity of women, and is also a violation of human rights, which is carried out by the Indonesian National Police (POLRI) towards female police officer candidates as well as the Indonesian National Armed Forces (TNI) towards female soldier candidates. Therefore, two problems arise in this research, namely what kind of obligations and responsibilities does Indonesia have in regards to providing legal protection for women according to international law, and how is the legality of the practice of the virginity tests carried out by POLRI and TNI according to international law. This study uses a qualitative, normative-legal approach. The result of this study are as follows: The obligations and responsibilities that Indonesia has in regards to providing legal protection for women is mandated by Article 7 of UDHR, Article 4 letters d, e, f, and l of Declaration on the Elimination of Violence Against Women (DEVAW), Article 2 letters a, b, c, and f of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), as well as Article 3 and Article 26 of the International Covenant on Civil and Political Rights (ICCPR). In regards to the legality of the virginity tests carried out by POLRI and TNI, such practice violates article 1, article 2, article 5 of Universal Declaration of Human Rights (UDHR), article 1, article 2 section (3), article 3, and article 4 letter b of DEVAW, article 1 and article 2 letter d of CEDAW, article 7 of ICCPR, as well as article 16 and article 10 of the Convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (CAT).